Learning Urogenital Diseases in Oddity (LUDO)—a gamification-based innovation for learning urogenital diseases in emergency medicine - Asjad Mallick; Shahan Waheed (International Journal of Emergency Medicine, 2024)
Abstract Urogenital emergencies demand immediate attention within the field of emergency medicine, encompassing a range of critical conditions from ectopic pregnancies to kidney stones. Timely diagnosis and treatment are vital to prevent potential mortality and morbidity. However, due to the sensitive nature of these disorders and the cultural taboos surrounding them, accessing prompt medical care can be challenging. To bridge this gap, innovative gamification-based learning techniques, such as the Learning Urogenital Diseases in Oddity (LUDO), have been introduced for emergency medicine residents (Chou, What is gamification? Yukai Chou: Gamification and behavioral design, n.d.; Gamification '13: Proceedings of the first international conference on gameful design, research, and applications, 2013). LUDO is a timed, gamified exercise that offers residents an interactive and engaging platform to enhance their clinical knowledge related to urogenital disorders. Adapted from the well-known board game, LUDO fosters learning, collaboration, and cooperation among residents. This format is highly customizable and can be utilized by various learning groups. Participants, emergency medicine residents from different academic years, formed four teams, each distinguished by a unique color. The exercise utilized simple and accessible materials, including a LUDO board, LED stopwatch, laptop, colored hats, and a desk bell. Teams advanced their tokens through the board by correctly answering urogenital disorder-related questions within a specified time frame. LUDO’s objectives extended beyond token movement, assessing essential skills such as teamwork, time management, resource utilization, and strategic decision-making. The option to seek external resources, limited to five times per team, added an element of strategy. Facilitators evaluated participants’ performance through questionnaires and Likert scales. The results revealed that LUDO effectively promoted teamwork, communication, leadership, and problem-solving among emergency medicine residents. Resident feedback was overwhelmingly positive, with interest in adopting this format for other educational modules. The gamified approach encouraged engagement and motivation, with immediate feedback ensuring continuous learning. In conclusion, the incorporation of the LUDO gamified format provides an enjoyable and interactive learning experience for emergency medicine residents. It enhances engagement, fosters teamwork, and facilitates the rapid assimilation of crucial knowledge related to urogenital diseases. This adaptable approach holds promise for improving resident training in various clinical scenarios.